Elastic phonon dephasing effect on spin transport in 2D hexagonal lattice topological insulator. (April 2021) - Rahaman, MdIstiaque; Alam, Mahbub
Abstract: 2D hexagonal lattice Topological Insulator (TI) shows topologically protected spin polarized edge transport while the bulk of the material remains insulating. The suppression of backscattering of electrons makes the edge transport of electrons robust against any perturbation. Elastic phonon dephasing represents a generalized scattering and dephasing mechanism. In this work, we have illustrated the effect of elastic phonon dephasing on the transport of electron in 2D hexagonal lattice TI using Non Equilibrium Green's Function (NEGF) formalism. The transmission was found to be unity (1) and the phase of the electron remained coherent even after strong phonon dephasing. The results of this paper indicate the suitability of TI in future dissipationless coherent nanoelectronic devices. Highlights: TIs suppress backscattering of electrons and shows robust transport against any perturbation. Elastic phonon dephasing represents a generalized scattering and dephasing mechanism. The Effect of elastic phonon dephasing on the transport of electron in 2D hexagonal lattice TI was found. Non Equilibrium Green's Function (NEGF) formalism has been used. The transmission was found to be unity (1) and the phase of the electron remained coherent.